Farmer and Farm Worker Perceptions of Land Reform and Sustainable Agriculture in Tajikistan - World Bank (Washington, DC, 2012)
The objectives of the study are to assess the impact of operational efforts in farmland restructuring and sustainable agricultural land management on vulnerability amongst rural households in Tajikistan; and to provide context and improve strategies for current operations in land reform, rural growth and sustainable land management given the challenges of economic transition, institutional, economic and environmental fragility, and the emerging risks of climate change. Low levels of assets and capabilities, as well as unsupportive institutional arrangements, constrain the options of the rural poor. Rural vulnerability both affects, and is affected by, household and community access to and use of land and other natural resources. Considerable theoretical literature can be found on the relationship between environmental management of agricultural production and rural vulnerability. This study examines the results and synergies of operational, field-level interventions in land tenure, sustainable land management and agricultural production. Limited management control over farmland, land degradation and low levels/low diversification of other assets are considered to be key drivers of rural vulnerability. A key focus, therefore, is to examine the effectiveness of strategies resulting from interventions to improve the incentive framework for farmers to help ensure livelihood security. The study seeks to examine linkages between operational efforts to secure family-based land tenure and other agricultural livelihood asset accumulation, and capacities to respond to shocks and stresses as seen in perceptions held by farmers and farm workers, in entrepreneurial behavior and adoption of sustainable land management practices. In the post-Soviet context, land-related family/household-based rights and responsibilities are considered particularly important motivations for sustainable natural resource management and building rural resilience.